Peranan Kepala Madrasah sebagai Pemimpin Dalam Pendidikan - Suyono, Suyono; Afrilia, Afnadilla; Eka Putri, Aldilla Rozias; Khairuna, Nadya (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The head of the madrasa as an educational figurehead is the subject of this study. Understanding the role that the head of the madrasa at MDTA AL WASHLIYAH KLAMBIR LIMA KAMPUNG plays in creating a curriculum that is in line with educational objectives is the primary focus of the discussion. As per the subjective methodology, the presence of specialists in the field is significant as an immediate instrument as an information gatherer from perception talks with and is effectively associated with research utilizing information assortment procedures via perception, meetings, and documentation as an eyewitness for the information that has been acquired from the consequences of meetings on the job the chief as top of the madrasa at MDTA AL WASHLIYAH KLAMBIR LIMA KAMPUNG. In view of the exploration, it tends to be presumed that school administrators assume a significant part in working on the nature of schooling, additionally including as teachers, chiefs, directors, bosses, pioneers, trend-setters, and inspirations to accomplish ideal objectives. Keywords: leadership, principal, role